Semantic Field of Teacher Terms in Ta`lim al-Muta`'allim Book by Sheikh Al-Zarnuji - Wahdan Abdul Manan; Abdul Hadi; Zulli Umri Siregar; Anwer Rakan Shallal (Arabiyyatī: Journal of Arabic Language Education, 2024)
Ta'lim Muta'allim is a book written by Shaykh al-Zarnuji that delves into the manners and guidelines for studying according to Islamic teachings. Throughout the text, the term "teacher" is extensively used with various equivalents, such as مدرس، معلم، أستاذ، شيخ and أهل العلم. This study aims to analyze the meanings of these terms in the book using semantic field theory to understand the relationship between the meanings of different words. This will help identify the relationships and differences between each of these terms. The research method used is qualitative, involving data collection techniques such as documentation and quotations. The data analysis method employed is semantic field analysis. The research results show that the lexemes أستاذ، معلم، شيخ، مدرس, and أهل العلم have many similarities, including the shared meaning of "teacher” although the meaning of each lexeme can change according to the context. Additionally, there are fundamental differences between each lexeme, serving as both characteristics and differentiators.